2009
DOI: 10.1128/jvi.02177-08
|View full text |Cite
|
Sign up to set email alerts
|

Proteinase 2AproIs Essential for Enterovirus Replication in Type I Interferon-Treated Cells

Abstract: The Picornaviridae family comprises a diverse group of small RNA viruses that cause a variety of human and animal diseases. Some of these viruses are known to induce cleavage of components of the innate immune system and to inhibit steps in the interferon pathway that lead to the production of type I interferon. There has been no study of the effect of picornaviral infection on the events that occur after interferons have been produced. To determine whether members of the Enterovirus genus can antagonize the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 65 publications
2
47
1
Order By: Relevance
“…7B). Our findings could also explain the recent observation that 2A pro of poliovirus and EV70 is essential for viral replication in interferon-treated cells (47). However, we found that 2A pro could not directly digest IFNAR1 in host cells (data not shown), suggesting an indirect interaction among 2A pro , IFNAR1, and undefined molecule(s).…”
Section: Discussioncontrasting
confidence: 52%
“…7B). Our findings could also explain the recent observation that 2A pro of poliovirus and EV70 is essential for viral replication in interferon-treated cells (47). However, we found that 2A pro could not directly digest IFNAR1 in host cells (data not shown), suggesting an indirect interaction among 2A pro , IFNAR1, and undefined molecule(s).…”
Section: Discussioncontrasting
confidence: 52%
“…Overall, our data suggest that type I IFN can induce a PKR-independent pathway to block VACV protein translation and that this pathway can be inhibited by K1L and C7L. Interestingly, some recent studies with norovirus and picornavirus also suggest that a PKR-independent pathway is induced by type I IFN to inhibit protein translation in cells infected by these RNA viruses (8,20). Identification of the target for K1L and C7L may lead to the identification of a novel antiviral host factor/pathway that has broad antiviral effects.…”
Section: C7lmentioning
confidence: 76%
“…Remarkably, 2A protein of cardioviruses, being nonessential though important (69,90,108), also exhibits antihost functions by inhibiting cell translation (44). 2A protease proteins of enterovirus and rhinovirus (unrelated to 2A proteins of cardioviruses), though apparently essential (70), also perform a set of anti-defensive functions very similar to those exhibited by L proteins of cardioviruses and aphthoviruses, namely the inhibition of host translation (59), the disruption of controllable nucleocytoplasmic traffic (12,75), the suppression of interferon action (71), and others (56). We propose that L proteins of aphthoviruses as well as 2A proteins of cardioviruses, enteroviruses, and rhinoviruses also be included in the group of security proteins.…”
Section: Apoptosis-triggering and Apoptosis-preventing Functions Of Cmentioning
confidence: 99%